2007
DOI: 10.1021/jp072625q
|View full text |Cite
|
Sign up to set email alerts
|

Change in Titania Structure from Amorphousness to Crystalline Increasing Photoinduced Electron-Transfer Rate in Dye-Titania System

Abstract: Thin titania gel films containing well-dispersed fluorescein dye were prepared by the sol−gel method and treated with steam to promote crystal growth of the titania particles. It is known that steam treatment converts the titania structure from amorphousness to crystalline. In the present study, such change is found to increase the rate of the photoinduced electron transfer from and to dispersed fluorescein dye molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 19 publications
4
71
0
Order By: Relevance
“…Nishikiori et al [64] found that an increase in the overall crystallinity of TiO 2 nanoparticles increased the surface quality of the nanoparticles, which improved the anchoring geometry of the dye on their surfaces and led to faster electron injection. However, back electron transfer via recombination with oxidized dye molecules, which decreases the quantum yield of photon-to-current conversion, was also enhanced as the crystallinity of the TiO 2 nanoparticles was increased.…”
Section: Dye Sensitizationmentioning
confidence: 99%
“…Nishikiori et al [64] found that an increase in the overall crystallinity of TiO 2 nanoparticles increased the surface quality of the nanoparticles, which improved the anchoring geometry of the dye on their surfaces and led to faster electron injection. However, back electron transfer via recombination with oxidized dye molecules, which decreases the quantum yield of photon-to-current conversion, was also enhanced as the crystallinity of the TiO 2 nanoparticles was increased.…”
Section: Dye Sensitizationmentioning
confidence: 99%
“…The carboxylate of fluorescein covalently bonding to the titania surface has been detected on by XPS analysis [29]. The absorbance decreased, the spectral peak of the film was red-shifted from around 480 to 485 nm, and the absorption band appeared at 500−600 nm by the steam treatment [14][15][16]30]. These results indicate that the anion was preferentially desorbed from the inside of the titania gel film because the species was weakly trapped in the pores of the gel.…”
Section: Effects Of Steam Treatmentmentioning
confidence: 99%
“…We strongly suggest that the fluorescein molecules formed a chelate complex with the titanium species on the titania surface to induce the interaction between their orbitals in the steam-treated electrodes based on the spectral red-shift. This interaction caused the ligand to metal charge transfer (LMCT) interaction and the fast electron injection to the titania conduction band [8,9,16,30].…”
Section: Dye-titania Interactionmentioning
confidence: 99%
“…The xanthene dye-dispersing titania gel was prepared without heating from a titanium alkoxide sol containing the dye molecules by the sol-gel method [27][28][29][30][31]. Xanthene dyes as laser dyes are available materials for utilizing photoenergy due to their high absorption and fluorescence efficiencies in various visible light regions [32].…”
Section: Introductionmentioning
confidence: 99%
“…Xanthene dyes as laser dyes are available materials for utilizing photoenergy due to their high absorption and fluorescence efficiencies in various visible light regions [32]. It was reported that the hydrothermal treatment of a dye-dispersing amorphous titania film remarkably improved the photoelectric conversion efficiency due to not only its crystallization but also the dye-titanium complex formation [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%